Efektivitas Uap Minyak Kayu Putih untuk Menurunkan Sesak Nafas pada Penderita Asma : Literatur Review - Putri Nurfitriani; Vika Aulia Pratiska; Vinne Maharani; Nabilla Larasyati; Achmad Chudaivih; Muhammad Asyrofi (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Asthma is a respiratory disease affecting 339 million people worldwide, which can be treated through various methods, including eucalyptus oil vapor, a non-pharmacological therapy. A literature review examining the effectiveness of eucalyptus oil vapor in reducing breathlessness among asthma patients, conducted using PubMed and Google Scholar databases, analyzed six articles from a pool of 280. Research findings revealed that eucalyptol (cineole) content possesses mucolytic and bronchodilatory properties, and vapor benefits include expanding respiratory passages, thereby facilitating breathing. Consequently, eucalyptus oil vapor emerges as an efficient self-management method for asthma patients, presenting no known side effects